1986
DOI: 10.1007/bf02441620
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pulse-wave velocity and arterial elasticity

Abstract: Pulse wave velocity (PWV) was measured in situ in 11 isolated canine common carotid arteries. Seven arteries exhibited a linear PWV vs. pressure function at pressures ranging from 0 to 200 mmHg. Four arteries yielded a linear relationship between PWV and pressure between 1 and 100 mmHg; for these vessels the relationship was nonlinear at higher pressures. Seven arteries (five from the group which was linear up to 200 mmHg and two from the group which was linear up to 100 mmHg) were excised and pressure/volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 2 publications
1
33
0
1
Order By: Relevance
“…Fukui et al carried out a series of numerical simulations with fluid-structure interaction on a straight vessel model of limited length and finite wall thickness with blood flow and demonstrated that the Moens-Korteweg equation is in good agreement with their computational model for PWVs up to 10 m/s irrespective of the tube wall thickness (38). Callaghan et al showed that in the canine common carotid artery, which is dimensionally similar to the phantom used for our experiments, PWV values as predicted by the Moens-Korteweg equation after measurement of the vessel elastic modulus agreed well with values derived from intravascular pressure measurements over a relatively wide range of pressures (39). In the descending aorta, Duprez et al confirmed adherence of the Moens-Korteweg equation to MR-derived PWV values in a middle-aged cohort of healthy volunteers (40).…”
Section: Discussionsupporting
confidence: 78%
“…Fukui et al carried out a series of numerical simulations with fluid-structure interaction on a straight vessel model of limited length and finite wall thickness with blood flow and demonstrated that the Moens-Korteweg equation is in good agreement with their computational model for PWVs up to 10 m/s irrespective of the tube wall thickness (38). Callaghan et al showed that in the canine common carotid artery, which is dimensionally similar to the phantom used for our experiments, PWV values as predicted by the Moens-Korteweg equation after measurement of the vessel elastic modulus agreed well with values derived from intravascular pressure measurements over a relatively wide range of pressures (39). In the descending aorta, Duprez et al confirmed adherence of the Moens-Korteweg equation to MR-derived PWV values in a middle-aged cohort of healthy volunteers (40).…”
Section: Discussionsupporting
confidence: 78%
“…The expression satisfying c 2 < γ 1 would recover the Moens-Korteweg formula c 0 = 3µH/(2ρ f R) for the pulse wave velocity in arteries if we took the further limit r ∞ → 1, λ 2∞ → 1, ρ → 0. This velocity value and its various improved forms [28] are often used in the medical community as a measure of the arterial stiffness and a risk factor for cardiovascular morbidity and mortality [29]. Figure 2 shows the fate of the four roots given by (3.4) as v f∞ is increased from 0.…”
Section: Dispersion Relation For Linear Travelling Wavesmentioning
confidence: 99%
“…The pressure pulse propagation wave speed is modulated primarily by 2 parameters, local compliance and downstream resistance. [13][14][15][16][17][18][19] For short-term changes in PVR (as would occur with pulmonary vasodilators), no immediate morphological changes and, consequently, no significant local compliance changes in the PAs are expected. As a result, any changes in pressure propagation before and after early treatment would be primarily due to changes in downstream resistance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…14,15,17 However, changes in local pressure (and so local pressure gradient) due to the changes in the pulse propagation wave speed should also affect local velocities within the artery due to the close association between velocity and pressure fields. 17,19,20 By extension, pressure pulse propagation should also cause an equivalent Vel prop .…”
Section: Theoretical Backgroundmentioning
confidence: 99%